A proposed service level agreement parameters for business to customer E-Commerce cloud - Busalim, Abdelsalam H. (2014)
Cloud computing provides a large pool of accessible resources (hardware, platform, software) in a form of services. It became a cost effective alternative to the traditional IT infrastructure. Nowadays, as more and more e-commerce companies delegate their task to cloud providers, Services Level Agreement (SLA) became an important aspect between the cloud consumer and cloud provider, the dynamic nature of cloud computing needs to continue monitoring of the services. The restricted choice of appropriate parameters in SLA affects the interacting of end user with cloud services and creates risks of user data. End users are concerned about their data and how it will be stored in cloud and how the data is recovered in the case of failure of disaster. However, none of SLAs considers the end user view while conducting the SLA document. The objective of this study is to propose SLA framework for B2C ecommerce cloud with integration of parameters which consider the end user perspective. In order to achieve this objective, this study has explored the SLA parameters with the objectives of these parameters as suggested by previous researchers. B2C ecommerce cloud SLA framework refined with those tested parameters, and SLA document has been designed as a proof of concept This research hopes to provide a protection to the end user when interact with e-commerce cloud websites by applying this SLA framework.